Integrating Cash Waqf Linked Green Sukuk with Contract Farming: A Strategy Model for Sustainable Agriculture - Syahrir Akbar; Gevin Kurniawan; Rehan Perdana Putra (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2025)
The agricultural sector remains a backbone of developing economies, including Indonesia, yet faces persistent challenges such as low productivity, unequal infrastructure, and unstable Farmers’ Exchange Value (NTP). Meanwhile, the potential of Islamic social finance through cash waqf and sharia-based instruments is still underutilized for sustainable development. This study proposes a model linking Cash Waqf Linked Green Sukuk (CWLGS) with contract farming as a financing strategy for sustainable agriculture based on maqāṣid al-sharī‘ah. CWLGS integrates cash waqf managed by Islamic Financial Institutions Receiving Cash Waqf (LKS-PWU) and invested in green sukuk to finance environmentally friendly projects. The returns are distributed by nazir to support farmers’ capital, production facilities, and mentoring within contract farming schemes involving state or regional enterprises (BUMN/BUMD). Using a qualitative descriptive approach, this research applies literature review, Business Model Canvas, stakeholder mapping, and SWOT analysis. The findings show dual benefits: maintaining the waqf principal and providing sustainable financing for agriculture. Implementation opportunities arise from sharia credibility, regulatory support, and green investment trends, while challenges include managerial capacity, waqf literacy, and market or environmental risks. Optimization strategies involve human resource development, commodity diversification, digital monitoring, and transparent reporting. From a maqāṣid al-sharī‘ah perspective, the model preserves religion, life, intellect, lineage, and wealth, serving as an innovative sharia-based mechanism for sustainable agriculture and SDGs achievement in Indonesia. Keywords: Cash Waqf, Contract Farming, Green Sukuk, Sustainability